Influence of environment on testing of hydraulic sealers. Issue 1 (December 2017) - Kebudi Benezra, Mira; Schembri Wismayer, Pierre; Camilleri, Josette
Abstract In vitro material testing is undertaken by conducting a series of tests following procedures outlined in international standards. All material properties are measured in water; however biological behavior is undertaken in alternative media such as Dulbecco's modified eagle medium (DMEM) or simulated body fluid. The aim of this study was to characterize four dental root canal sealers and study their properties in different media. Four dental root canal sealers were assessed. They were characterized by a combination of techniques and the sealer properties were tested as specified by ISO 6876 (2012) and also in alternative media. The sealer biocompatibility was measured by cell function and proliferation assays of elutions. All sealers complied with ISO specifications. The material properties were effected by the type of soaking medium used and the surface micromorphology and elemental composition were dependent on the soaking solution type. Both BioRoot and MTA Fillapex showed cytotoxicity which reduced at higher dilutions. The material chemistry, presentation, environmental conditions and testing methodology used affected the sealer properties. Standards specific to sealer type are thus indicated. Furthermore the methodology used in the standard testing should be more relevant to clinical situations.